"Boom, Headshot!": Violent first‐person shooter (FPS) video games that reward headshots train individuals to aim for the head when shooting a realistic firearm. Issue 1 (17th September 2018) - Bushman, Brad J.
Abstract : When shooting a gun at a human target, firearms training instructors teach individuals to shoot for the upper torso because it is the largest lethal target on the human body. In contrast, violent first‐person shooter (FPS) video games reward players for headshots. The head is the smallest lethal target, and requires careful aim to hit. In this experiment, participants were randomly assigned to play a violent FPS game with humanoid targets that rewarded headshots, a nonviolent shooting game that punished hits to bull's‐eye targets with faces, or a nonviolent non‐shooting game. After gameplay, participants shot 16 "bullets" from a realistic gun at a life‐sized human‐shaped mannequin. Participants were told to hit the mannequin with as many bullets as possible, but they were not told where to aim. Consistent with operant conditioning theory, participants who played a violent FPS game that rewarded headshots had the most hits to the mannequin's head. Participants whose favorite video games were violent shooting games also had the most hits to the mannequin's head. These findings suggest that FPS games that reward headshots can influence people to aim for the head with a realistic gun after the game is turned off, even though the head is a much smaller target to hit and they are much less likely to hit another body part if they miss. FPS games are often used to train soldiers and police officers, but these findings suggest that such games might train individuals to hit the wrong part of the body.